Employment Social Protection for Indonesian Migrant Workers in South Korea: Probability and Policy Review - Sucihatiningsih Dian Wisika Prajanti; Edi Kurniawan; Talitha Widiatningrum (Jurnal Abdimas, 2024)
The Government-to-Government (G2G) program significantly increases the number of Indonesian Migrant Workers (PMI) in Korea. As a developed country, South Korea is committed to protecting all workers in its territory, including migrant workers from Indonesia. However, the employment social security of the South Korean government is not fully able to cover the risks and needs of PMI. Protecting migrant workers' rights to social security is important. It is also the responsibility of the Indonesian government through BPJS Employment, not only to ensure equal treatment in social security for migrant workers but also to expand social security coverage for populations that are currently unprotected. Therefore, it is important for employment social security administrators to increase the probability of migrant workers becoming BPJS Employment participants. Using the logistic regression method and Sakernas data for August 2021, it was found that migrant workers who work in the formal sector, with work contracts, and have BPJS Health membership have a higher tendency to become Employment Social Security participants.